2012
DOI: 10.2217/nnm.11.139
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Targeted Imaging and Delivery of Camptothecin Using Cetuximab-Conjugated Multifunctional Plga-Zns Nanoparticles

Abstract: Background: Targeted cancer therapy has been extensively developed to improve the quality of treatment by reducing the systemic exposure of cytotoxic drug. Polymeric nanoparticles with conjugated targeting agents are widely investigated because they offer tunability in particle size, drug release profile and biocompatibility. Materials & methods: Here, we have prepared targeted multifunctional nanoparticles composed of a poly(lactic-co-glycolic acid) matrix, ZnS:Mn2+ quantum dots and camptothecin, and targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Binding of cetuximab to EGFR also induces receptor internalization [10]. Cetuximab conjugated anticancer nanocarriers successfully enhance cytotoxic activity in EGFR-positive cancers [11,12]. However, binding of the Fc region of mAbs to Fc receptors on mononuclear phagocyte system can result in uptake of the mAb and clearance of mAb and conjugated nanoparticles from circulation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Binding of cetuximab to EGFR also induces receptor internalization [10]. Cetuximab conjugated anticancer nanocarriers successfully enhance cytotoxic activity in EGFR-positive cancers [11,12]. However, binding of the Fc region of mAbs to Fc receptors on mononuclear phagocyte system can result in uptake of the mAb and clearance of mAb and conjugated nanoparticles from circulation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al (2010) demonstrated the potential application of cetuximab-conjugated magneto-fluorescent silica nanoparticles for the detection of EGFR-expressing colon cancer using in vivo imaging approaches. Targeted delivery of nanoparticles loaded with chemotherapeutics to tumor cells has also been sought by using mAbs against EGFR (Deepagan et al 2012). The results suggest that these targeted nanocarriers systems hold a promising role in management of cancers overexpressing EGFR.…”
Section: Resultsmentioning
confidence: 99%
“…Yaghoub Safdari,1,7 Vahideh Ahmadzadeh, 2,3 Masoumeh Khalili, 4 Hossein Zarei Jaliani, 5 Vahid Zarei, 6 and Vahid Erfani-Moghadam time, patients acquire resistance to such inhibitors for several reasons, including point mutations in the EGFR intracellular tyrosine kinase domain which annuls the binding of TKI to EGFR, mutation and subsequent activation of Kirsten rat sarcoma viral oncogene (KRAS), epithelial-to-mesenchymal transformation, gene amplification of mesenchymal-to-epithelial transformation (MET) factor and so forth (17)(18)(19)(20). To overcome TKI resistance in lung cancer, Lu and colleagues produced a single-chain format of nimotuzumab, an anti-EGFR monoclonal antibody, and used it to specifically deliver siRNA molecules to EGFR-expressing cells to suppress MET, EGFR and KRAS gene expression (21).…”
Section: Use Of Single-chain Antibody Derivatives For Targeted Drug Dmentioning
confidence: 99%